Design and Research on Reliability-validity for 3S Intraoperative Risk Assessment Scale of Pressure Sore - 高兴莲 胡娟娟 马琼 吴荷玉 王曾妍 李婷婷 沈剑辉 杨英 (Journal of Huazhong University of Science and Technology. Medical sciences, 2015)
The reliability and validity of risk assessment scale（RAS） of pressure sore during 3S surgery were investigated. RAS of pressure sore was designed independently during 3S surgery. Five operating room nursing experts were selected to consult and detect face validity. Convenient and purposive sampling of 707 samples was conducted. Cronbach＇s alpha was used to measure content reliability and evaluate the internal consistence of RAS. The structural reliability was investigated by exploratory factor analysis method. The results showed that the content validity index was 0.92, and Cronbach＇s alpha of content reliability was 0.71. Structural validity, detected by Bartlett sphericity test, was 135.3 for 707 samples with the difference being statistically significant（P〈0.01）. KMO value was 0.729. The accumulative variance contribution ratio of common factor was 64.63%. The exploratory factor analysis showed the factor load of every clause was larger than 0.596. It was concluded that RAS of pressure sore for 3S surgery has better validity and reliability, and it could be used for evaluating and screening the high risk patients with pressure sores during surgery in order to efficiently reduce the occurrence of pressure sore during surgery. RAS of pressure sore for 3S surgery is worth to be popularized.